Lower serum GPX4 and GSH/GSSG ratio are associated with poor prognosis in severe community-acquired pneumonia - Wei Zhu; Kunyu Wang; Xiaolei Xing; Xinxin Xu; Yonghui Liang; Ke Wang (European Journal of Medical Research)
Abstract Objectives Disruption of redox homeostasis and ferroptosis have been increasingly implicated in the pathogenesis of inflammatory lung injury. Glutathione peroxidase 4 (GPX4) and the ratio of reduced to oxidized glutathione (GSH/GSSG) are key regulators in this process. However, the clinical significance of ferroptotic factors in severe community-acquired pneumonia (CAP) is still lacking. This study investigated the prognostic value of serum glutathione peroxidase 4 (GPX4) and the GSH/GSSG ratio in severe CAP. Methods A prospective cohort of 267 ICU-admitted severe CAP patients (2021–2023) was analyzed. Serum GPX4 and GSH/GSSG were measured within 24 h of admission. Patients were grouped by 30-day survival. Statistical analyses included comparative tests, Spearman correlation, ROC curves, Kaplan–Meier survival, and multivariate logistic regression. Results Among 267 patients, 79 (29.6%) died within 90 days. Deceased patients had significantly lower GPX4 and GSH/GSSG (both P < 0.001). GPX4 was lower in COVID-19 cases (P = 0.022), while GSH/GSSG showed no such difference. GPX4 and GSH/GSSG were moderately correlated (r = 0.301, P < 0.001). ROC analysis showed good predictive accuracy for 30-day mortality, with an AUC of 0.778 for GPX4, 0.780 for GSH/GSSG, and 0.841 for their combination. Kaplan–Meier analysis indicated lower survival with reduced GPX4 or GSH/GSSG (P < 0.01). Multivariate analysis identified lower GPX4, GSH/GSSG, COVID-19, higher SOFA scores, prolonged ICU stay, and mechanical ventilation as independent mortality risk factors. Conclusions Lower serum GPX4 and GSH/GSSG ratios are associated with increased mortality in severe CAP.